2022
DOI: 10.1136/bmj-2022-073070
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mRNA-1273, BNT162b2, and BBIBP-CorV vaccines against infection and mortality in children in Argentina, during predominance of delta and omicron covid-19 variants: test negative, case-control study

Abstract: Objective To estimate the effectiveness of a two dose vaccine schedule (mRNA-1273, BNT162b2, and BBIBP-CorV) against SARS-CoV-2 infection and covid-19 related death and short term waning of immunity in children (3-11 years old) and adolescents (12-17 years old) during periods of delta and omicron variant predominance in Argentina. Design Test negative, case-control study. Setting Database of the National Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“… 10 Data showing similar results have also been reported from multiple countries such as Argentina, Denmark, France, and Qatar, with some studies estimating 10-fold reductions in MIS-C with vaccination. 42 , 44 , 45 , 50 , 51 Although infection-based outcomes showed decreased effectiveness during Omicron, a decreased rate of MIS-C with vaccination has been described during Alpha, Delta, and Omicron predominance. 10 , 50 Most studies did not report many, if any fatalities; however, data from Argentina suggest a mortality benefit from vaccinations (66.9%-97% protection depending on age).…”
Section: Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Data showing similar results have also been reported from multiple countries such as Argentina, Denmark, France, and Qatar, with some studies estimating 10-fold reductions in MIS-C with vaccination. 42 , 44 , 45 , 50 , 51 Although infection-based outcomes showed decreased effectiveness during Omicron, a decreased rate of MIS-C with vaccination has been described during Alpha, Delta, and Omicron predominance. 10 , 50 Most studies did not report many, if any fatalities; however, data from Argentina suggest a mortality benefit from vaccinations (66.9%-97% protection depending on age).…”
Section: Data Synthesismentioning
confidence: 99%
“… 10 , 50 Most studies did not report many, if any fatalities; however, data from Argentina suggest a mortality benefit from vaccinations (66.9%-97% protection depending on age). 51 …”
Section: Data Synthesismentioning
confidence: 99%
“…4 The protection against COVID-19-related death in our study was similar to data reported for children aged 5 to 11 years in other populational studies. 5,6 A limitation of our study is a possible underestimated VE against Omicron infection due to omitted vaccination time for most participants. Regardless of vaccine schedule, we observed low effectiveness in preventing Omicron infection in young people.…”
mentioning
confidence: 96%
“…Study after study in The BMJ and other major journals has indicated the effectiveness of this vaccine technology (doi:10.1136/bmj.o2865 doi:10.1136/bmj-2022-073070 doi:10.1136/bmj-2022-072065). 567 Now, a new study in The BMJ shows that maternal mRNA covid-19 vaccination during pregnancy protects infants against SARS-CoV-2 infection and hospital admission (doi:10.1136/bmj-2022-074035). 8…”
mentioning
confidence: 99%